2022
DOI: 10.21203/rs.3.rs-2170577/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simple and efficient preservation of fish environmental RNA in filtered water samples via RNAlater

Abstract: Environmental RNA (eRNA) analysis has recently received attention as a better means to infer the physiological status of a community and living biotic assemblages than environmental DNA (eDNA). However, eRNA is thought to be degraded more rapidly than eDNA, increasing the risk of false-negative detection and complicating large-scale eRNA sampling in the field. In addition, the need for a deep freezer (− 80°C or below) further limits the practical application of eRNA analysis in places that are not accessible b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The general assumption has been that the eRNA released by macroorganisms into the environment is labile and degrades too rapidly to be reliably detected or quantified (but see Cristescu, 2019). However, the RNA shed by macroorganisms into their surrounding environment can be successfully extracted and quantified (T. Jo et al, 2022; Kagzi et al, 2022; Littlefair et al, 2022; Marshall et al, 2021; Miyata et al, 2021; Tsuri et al, 2021; von Ammon et al, 2019; Wood et al, 2020). Despite this evidence supporting the extractability of eRNA, environmental transcriptomics, defined here as eRNA based gene expression profiling, remained untested.…”
Section: Introductionmentioning
confidence: 99%
“…The general assumption has been that the eRNA released by macroorganisms into the environment is labile and degrades too rapidly to be reliably detected or quantified (but see Cristescu, 2019). However, the RNA shed by macroorganisms into their surrounding environment can be successfully extracted and quantified (T. Jo et al, 2022; Kagzi et al, 2022; Littlefair et al, 2022; Marshall et al, 2021; Miyata et al, 2021; Tsuri et al, 2021; von Ammon et al, 2019; Wood et al, 2020). Despite this evidence supporting the extractability of eRNA, environmental transcriptomics, defined here as eRNA based gene expression profiling, remained untested.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current filter methods to detect environmental RNAs in water can mainly measure RNAs remaining in the filters, neglecting dissolved RNAs in the filtrates. Filters used for filtering water samples to measure environmental RNAs have different pore sizes, such as 0.2~0.22 µm (Wu and Liu, 2018;Wood et al, 2020;Hempel et al, 2022), 0.45 µm (von Ammon et al, 2019Tsuri et al, 2020;Miyata et al, 2021;Zaiko et al, 2022;Jo et al, 2022b;Miyata et al, 2022), 0.7 µm (Kagzi et al, 2022;Hechler et al, 2022;Jo et al, 2022a;Littlefair et al, 2022), 1.2 µm (Marshall et al, 2021;Zaiko et al, 2022), 1.6 µm (Pochon et al, 2017), and 5 µm (Zaiko et al, 2022). A study indicated that filters with different pore sizes could collect naked RNAs (Zaiko et al, 2022), but the RNA amounts in the filtrates were unknown in that study.…”
Section: Introductionmentioning
confidence: 99%